Effects of the use of gliricídia and phosphate rock on growth and N, P and K levels in okra and cucumber crops (Research, Society and Development, 2021)
The nutritional requirements of vegetables have caused losses to small and medium-sized family farmers in terms of reduced productivity and food security in society. In this sense, the objective was to evaluate the development of okra (Abelmoschus escurentes L.) and cucumber (Cucumis sativus L.) plants, using sheep manure associated with phosphate rock and gliricídia and the quantification of the levels of N, P and K in plant structures. The experiment was conducted at the Federal Institute of Science and Technology of Roraima - Campus Novo Paraíso, in a greenhouse, using pots with a capacity of 6 L-¹, filled with soil (Neosolo) collected from the 0-20 cm layer. The experimental design was a randomized block, with treatments arranged in a 2x2 factorial, composed of two levels of gliricídia (without gliricídia (S / G) and (with gliricídia (C / G) and two levels of phosphate rock (without rock) (S / R) and (with rock (C / R), with four repetitions, being distributed in the blocks in a completely randomized way. A dose of sheep manure, corresponding to 25 t ha-1, was added to the pots. The variables determined in the study were: plant height (cm), stem thickness (mm), number of leaves, fruit diameter (mm), fruit length (cm), fruit weight (g) and the contents of N, P and K in the plant and in the fruits The results found for the different treatments showed no differences It was observed that the standardization of the fertility of the pots directly interfered in the statistical results, this way, the farmers can renounce the use of the leaf of the gliricídia and of the rock phosphate, as long as he has sheep manure available.